The well symbol in the work "Hüsn ü Aşk" - Do?an, Ahmet (My University, 2005)
In Hüsn ü Ask poem (mesnevi), which showed the characteristic of "mirî mali"(creator's possesion) in the context of Sufism and Mevlevi, Seyh Gâlib in a metaphysical plot, around the circle of the character Ask narrated the inner transformation of human. In the work, Ask, who represents a disciple that is in the transition period, has faced to face with a series of hard difficulties as a result of this period. One of these difficulties is the well that Ask suddenly fell into. The well that Ask fell into is a special place he has to pass through in order to complete his mirac (improvement himself in the path to God). His falling in to the well indeed symbolizes his transition from the outer world to the inner world.
Hüsn ü Aşk'ta kuyu sembolü
Keywords: Hüsn ü Ask; Seyh Gâlib; Seyr-i sülûk.(the path reaching to God); Well